Urgensi Perlindungan Hukum Terhadap Hak Cipta dalam Industri Sinematografi - Kurniawati Rahayu; Romi Faslah (CV. ITTC INDONESIA, 2025)
Copyright, as part of Intellectual Property Rights (IPR), plays a vital role in protecting creative works, especially in the field of cinematography. Unfortunately, public awareness in Indonesia regarding the importance of copyright protection remains low, contributing to widespread violations such as film piracy, script plagiarism, and unauthorized use of film clips. This study aims to examine the importance of legal protection for copyright in the film industry and analyze the roles of key stakeholders including producers, directors, screenwriters, and music composers as copyright holders. Referring to Law No. 28 of 2014, this article also outlines the copyright registration procedure as a preventive measure to safeguard creative works. Adequate legal protection is believed to foster a healthy creative climate and provide legal certainty for creators. Therefore, increasing public awareness and education on copyright is essential to support the growth of the national creative industry.